Targeting IGF Perturbs Global Replication through Ribonucleotide Reductase Dysfunction - Rieunier, Guillaume; Wu, Xiaoning; Harris, Letitia E; Mills, Jack V; Nandakumar, Ashwin; Colling, Laura; Seraia, Elena; Hatch, Stephanie B; Ebner, Daniel V; Folkes, Lisa K; Weyer-Czernilofsky, Ulrike; Bogenrieder, Thomas; et al. (Cancer research (Chicago, Ill.), 2021)
Inhibition of IGF receptor (IGF1R) delays repair of radiation-induced DNA double-strand breaks (DSB), prompting us to investigate whether IGF1R influences endogenous DNA damage. Here we demonstrate that IGF1R inhibition generates endogenous DNA lesions protected by 53BP1 bodies, indicating under-replicated DNA. In cancer cells, inhibition or depletion of IGF1R delayed replication fork progression accompanied by activation of ATR-CHK1 signaling and the intra-S-phase checkpoint. This phenotype reflected unanticipated regulation of global replication by IGF1 mediated via AKT, MEK/ERK, and JUN to influence expression of ribonucleotide reductase (RNR) subunit RRM2. Consequently, inhibition or depletion of IGF1R downregulated RRM2, compromising RNR function and perturbing dNTP supply. The resulting delay in fork progression and hallmarks of replication stress were rescued by RRM2 overexpression, confirming RRM2 as the critical factor through which IGF1 regulates replication. Suspecting existence of a backup pathway protecting from toxic sequelae of replication stress, targeted compound screens in breast cancer cells identified synergy between IGF inhibition and ATM loss. Reciprocal screens of ATM-proficient/deficient fibroblasts identified an IGF1R inhibitor as the top hit. IGF inhibition selectively compromised growth of ATM-null cells and spheroids and caused regression of ATM-null xenografts. This synthetic-lethal effect reflected conversion of single-stranded lesions in IGF-inhibited cells into toxic DSBs upon ATM inhibition. Overall, these data implicate IGF1R in alleviating replication stress, and the reciprocal IGF:ATM codependence we identify provides an approach to exploit this effect in ATM-deficient cancers. SIGNIFICANCE: This study identifies regulation of ribonucleotide reductase function and dNTP supply by IGFs and demonstrates that IGF axis blockade induces replication stress and reciprocal codependence on ATM. GRAPHICAL ABSTRACT: http://cancerres.aacrjournals.org/content/canres/81/8/2128/F1.large.jpg.